The phylogenetic position of Chalcides ocellatus (Squamata: Scincidae) from Yemen and Somalia - Lavin, Brian R.; Papenfuss, Theodore J. (Zootaxa, 2012)
The skink Chalcides ocellatus (Forskal) is distributed around the Mediterranean region, Arabian Peninsula, and Horn of Africa. We examined C. ocellatus from Yemen and Somalia to clarify the biogeography of the species in the region of the Red Sea/Gulf of Aden. We examined 3612 bp of partial and complete mtDNA fragments (12S, 16S, ND1, cyt b, ND4, and adjacent tRNA) and 5380 bp of partial nuclear DNA fragments (BDNF, C-MOS, Rag1, PNN, and R35). Bayesian inference and Maximum-likelihood analysis placed the Somalia and Yemen specimens with those from the Eastern Mediterranean. We were unable to resolve a split between East African (Somalia) and Arabian (Yemen) populations with mtDNA, nuclear loci, and combined loci analyses.